Morphometric Study of Musanga cecropioides R. Brown and Myrianthus arboreus Palisot de Beauvois (Family Cecropiaceae) - JO Arusuraire; BL Nyananyo (Journal of Applied Sciences and Environmental Management, 2015)
Morphometric or Numerical taxonomic analysis of 56 quantitative and qualitative characters, obtained from Musanga cecropioides R. Brown and five species of Myrianthus, M. arboreus Palisot de Beauvois, M. holstii  Engler, M. libericus Rendle, M. preusii Engler and M. serratus (Trecul) Bentham was carried out by calculating  similarity and distance indices followed by cluster analysis and construction of a dendrogram for visual  appreciation of the taxonomic relationship among these species. The dendrogram showed close similarity among the Myrianthus species, with Musanga cecropioides clearly distinct from the Myrianthus species. This confirms the monotypic status of Musanga, with only one species, Musanga cecropioides.